Small HSPs at the crossroad between protein aggregation, autophagy and unconventional secretion: clinical implications and potential therapeutic opportunities in the context of neurodegenerative diseases - Bonavita, Raffaella; Vitale, Fulvia; Verdicchio, Luigi Vittorio; Williams, Sarah V.; Caporaso, Maria Gabriella; Fleming, Angeleen; Renna, Maurizio (Frontiers in Cell and Developmental Biology, 2025)
Neurodegenerative diseases (NDs) such as Alzheimer’s, Parkinson’s and Huntington’s diseases as well as ataxias and fronto-temporal disorders are all characterized by the progressive accumulation of protein aggregates (amyloids) into inclusions bodies. In addition, recent experimental evidence is challenging the conventional view of the disease by revealing the ability of some of these disease-relevant proteins to be transferred between cells by means of extracellular vesicles (EVs), allowing the mutant protein to seed oligomers involving both the mutant and wild type forms of the protein. Abnormal secretion and levels of EVs are closely related to the pathogenesis of neurodegenerative diseases and contribute to disease progression. Numerous studies have proposed EVs as therapeutic targets or biomarkers for neurodegenerative diseases. In this review, we summarize and discuss the role of small heat shock proteins (sHSPs) and autophagy in cellular quality control and turn-over of the major aggregation-prone proteins associated to neurodegenerative disorders. We also highlight the advanced research progress on mechanisms regulating unconventional secretion, secretory autophagy and EVs biogenesis and their contribution in the pathological processes underlining these diseases. Finally, we outline the latest research on the roles of EVs in neurodegenerative diseases and their potential diagnostic and therapeutic significance for the treatment of these clinically relevant conditions.